On Analysis of Single Solution for a Class of BVP with Generalized Caputo-Katugampola Fractional Derivative (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we endeavor to simulate the existence of a single solution for a BVP for Caputo-Katugampola fractional derivative in the manner theorem of contraction of Banach. We extrapolate similar examples to interpret the conclusions reached.